Abuse in New Religious Movements - Harvey, Sarah (Cambridge University Press, 2026)
This Element analyses issues of abuse in new religious movements (NRMs). It argues that certain factors can be intensified in NRM contexts, not least propensities for separation from wider society, teachings on unique legitimacy and exclusivity, and charismatic authority. This title is also available as Open Access on Cambridge Core.